Interaction Between Mesenchymal Stem Cells and Retinal Degenerative Microenvironment - Lin, Yu; Ren, Xiang; Chen, Yongjiang; Chen, Danian (Frontiers in Neuroscience, 2021)
Retinal degenerative diseases (RDDs) are a group of diseases contributing to irreversible vision loss with yet limited therapies. Stem cell-based therapy is a promising novel therapeutic approach in RDD treatment. Mesenchymal stromal/stem cells (MSCs) have emerged as a leading cell source due to their neurotrophic and immunomodulatory capabilities, limited ethical concerns, and low risk of tumor formation. Several pre-clinical studies have shown that MSCs have the potential to delay retinal degeneration, and recent clinical trials have demonstrated promising safety profiles for the application of MSCs in retinal disease. However, some of the clinical-stage MSC therapies have been unable to meet primary efficacy end points, and severe side effects were reported in some retinal “stem cell” clinics. In this review, we provide an update of the interaction between MSCs and the RDD microenvironment and discuss how to balance the therapeutic potential and safety concerns of MSCs' ocular application.